Matemática discreta: tópicos de recorrências lineares e suas aplicações - Castro, Fabiano José de (2016)
I show this thesis linear recurrences starting with a brief historical review of the main authors of some problems of linear recurrences. Analyze elementary sequences, positional formulas, recursive methods, arithmetic and geometric progressions. Later, I will distinguish what are relations of relapses and recurrences following equations with the explanation of the solution of a recurrence, exposed in some instances and also the rst recurrence settings and second orders with their ratings. Soon after I'll discuss brie y the respect of some types of third-order recurrences and also see some generalizations to higher order. Treat, nishing this work, applications of recurrences using the foundations mentioned above and problems involving combinatorial.